Effects of Zinc Oxide Nanoparticle on Antioxidant System in Bean Leaves - Kirecci, Oguz Ayhan; Uzgen, Serdar; Okutan, Tuba; Yilmaz, Okkes (Kahramanmaras Sutcu Imam Univ Rektorlugu, 2025)
Nanotechnology can be most simply defined as technology at the nanoscale. Heavy metal stress often induces reactive oxygen species (ROS) and causes oxidative stress. Antioxidant enzymes, metabolites, flavonoids, carotenoids, polyols, cytosolic ascorbate, and peroxiredoxin play roles in ROS scavenging. Certain antioxidant enzymes such as catalase (CAT), ascorbate peroxidase (APX), superoxide dismutase (SOD), and glutathione reductase (GR) defend against metal toxicity. In this study, the effects of zinc nanoparticles on certain biochemical parameters in the leaves of bean (Phaseolus vulgaris L.) were examined. For this purpose, ZnO nanoparticle concentrations of 0.1 mM, 0.01 mM, and 0.001 mM were applied. At the end of 120 hours, malondialdehyde, proline, glutathione, total soluble protein, and the activities of superoxide dismutase and catalase enzymes were determined. As a result, all findings from this study revealed that ZnO nanoparticle applications activated antioxidant defense mechanisms in the leaves of Phaseolus vulgaris L. It was determined that the mentioned ZnO nanoparticle exhibited more pronounced effects, especially at lower doses. Nano-sized metals were found to exert toxic effects on the leaves of Phaseolus vulgaris L.
Keywords: Antioxidant system; Bean; Nanoparticle; Zinc oxide